Critical views on teaching and learning English around the globe : qualitative research approaches - Alvarez V., Jose Aldemar; Armanti, Cathy; Keyl, Shireen; Mackinney, Erin (Research in second language learning., 2016)
This volume takes a critical look at teaching and learning English across the globe. Its aim is to fill a gap in the literature created by the omission of the voices of those engaged in the everyday practice of teaching and learning English; those of students, teachers, and specialists. Three unique characteristics give this book broad appeal. They include - its inclusion of the perspectives and experiences of students and educators involved in the everyday practice of English language teaching and learning - its inclusion of the experiences of students and educators in both core and non-core English-speaking countries - its basis on original, qualitative studies conducted by scholars in different parts of the world including Europe, the Middle East, Asia, and the Americas Of particular interest to applied linguists, scholars from diverse fields such as English as a Foreign/Second Language, English as an International Language, anthropology and education, English education, sociolinguistics, and bilingual education will also find value in this book. Written in accessible language, it can be used in such courses as Applied Linguistics, Second Language Classroom Contexts, Bilingualism and Multilingualism, English Around the World, Research Methodologies in Second Language Acquisition, and Research in Second Language Pedagogical Contexts. In addition, by focusing on presenting research experiences that adopt several epistemological and theoretical approaches, the book provides teachers of research with a great tool to examine varied applications of qualitative methods, data collection, and analytic techniques. Thus it could also be used for courses in Field Research and Qualitative Methods.